Load demand management optimization for Accommodating Electric Vehicle - Km Seema Maurya; Dr. Imran Khan; Dr Malik Rafi (iJournals:International Journal of Software & Hardware Research in Engineering ISSN:2347-4890, 2026)
As the world paces towards environmental sustainability, the rapid adoption of electric vehicles, particularly in developing countries such as India, stands as a pillar of progress but also introduces complex challenges for the power distribution grid. This paper critically examines these challenges, focusing on demand-side management (DSM) load modelling as a strategic approach to accommodate the fluctuating demands of EV charging. It investigates the utilisation of advanced optimisation algorithms that promise to enhance grid stability by efficiently managing the additional load imposed by EVs. The narrative further explores the development of smart grid technologies, essential for the seamless EV integration into the power system. The paper also discussed the indispensable role of renewable energy sources in meeting the increased electricity demands, advocating for a symbiotic relationship between green transportation and sustainable energy generation. Through a comprehensive analysis, this paper aims to provide policymakers, energy sector professionals, and researchers with insightful strategies to navigate the complexities of EV integration. It underscores the importance of innovative solutions in building a resilient, efficient, and sustainable energy ecosystem that supports India’s ambitious EV adoption goals. This paper also suggests a methodology for stochastic modelling of EV charging load and its challenges related to their impact on the power distribution grid, focusing on DSM and grid integration strategies. This holistic approach addresses the immediate technical and infrastructural challenges and aligns with the long-term vision of achieving energy security and environmental sustainability.